2009
DOI: 10.1086/596067
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Association Study of an AIDS‐Nonprogression Cohort Emphasizes the Role Played byHLAGenes (ANRS Genomewide Association Study 02)

Abstract: To elucidate the genetic factors predisposing to AIDS progression, we analyzed a unique cohort of 275 human immunodeficiency virus (HIV) type 1-seropositive nonprogressor patients in relation to a control group of 1352 seronegative individuals in a genomewide association study (GWAS). The strongest association was obtained for HCP5 rs2395029 (P=6.79x10(-10); odds ratio, 3.47) and was possibly linked to an effect of sex. Interestingly, this single-nucleotide polymorphism (SNP) was in high linkage disequilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
190
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(205 citation statements)
references
References 29 publications
(36 reference statements)
12
190
2
1
Order By: Relevance
“…Polymorphisms in the ZNRD1 gene remained statistically significantly associated with the LTNP phenotype when HLA-A10 was introduced as a covariable in the analysis. In addition, the effect of HLA-A10 was not statistically significantly associated with progression, suggesting a more discrete effect (if any) and an independent role for ZNRD1, in accordance with the findings of other association studies [7,30,31,37]. Although the earlier studies were based on the complex spatial structure and linkage disequilibrium pattern of a relatively large region, we took a more focused approach on individual polymorphisms around the ZNRD1 gene, because of its demonstrated effect on HIV-1 replication in cell culture.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Polymorphisms in the ZNRD1 gene remained statistically significantly associated with the LTNP phenotype when HLA-A10 was introduced as a covariable in the analysis. In addition, the effect of HLA-A10 was not statistically significantly associated with progression, suggesting a more discrete effect (if any) and an independent role for ZNRD1, in accordance with the findings of other association studies [7,30,31,37]. Although the earlier studies were based on the complex spatial structure and linkage disequilibrium pattern of a relatively large region, we took a more focused approach on individual polymorphisms around the ZNRD1 gene, because of its demonstrated effect on HIV-1 replication in cell culture.…”
Section: Discussionsupporting
confidence: 90%
“…In the middle of such an intricate picture, however, several genetic polymorphisms have been described that clearly influence the outcome of HIV infection, specially in the HLA region, where ZNRD1 is located [7,31,36,37]. Genetic complexity and the high linkage disequilibrium of the region challenges the effect of ZNRD1 on HIV disease progression [32,37].…”
Section: Discussionmentioning
confidence: 99%
“…This idea has long been supported by both functional studies examining the response and quality of ES CD8 ϩ T cells (2, 3, 5, 10, 36-40) and genome-wide association studies identifying major histocompatibility complex class I alleles (such as HLA-B*57 and HLA-B*27) (41)(42)(43)(44)(45)(46). In addition, these protective HLA alleles have been shown to be overrepresented in multiple ES cohorts (5,41,(47)(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 97%
“…Genome-wide association studies (GWASs) have shown that variation in HLA class I region has the greatest differential influence on HIV viral load control (17)(18)(19)(20)(21)(22). Delineating the precise "causal" locus/loci, however, is problematic in the rich environment of functionally related, highly polymorphic, and tightly linked disease candidate loci located within the MHC.…”
Section: Significancementioning
confidence: 99%